MALE-FEMALE EFL STUDENTS’ PERCEPTION ON THE USE OF AUDIO VISUAL AIDS TO IMPROVE THEIR VOCABULARY MASTERY - Firda Fauziah; Etika Rachmawati; Misbahudin Misbahudin (Universitas Galuh, 2018)
This study attempted to investigate male-female EFL students’ perception on the use of audio visual aids in learning vocabulary mastery. The aims of this study were to finding out the male EFL students’ perception on the use of audio visual aids in learning vocabulary, the female EFL students’ perception on the use of audio visual aids in learning vocabulary, and how audio visual aids help students in improving their vocabulary mastery. The participants were 19 students at the tenth grade students in one of senior high schools in Ciamis. This study employed one type of qualitative strategies that was using case study. The writer used three instruments to gain the data, they were questionnaire, interview and observation. The result for the first question asserted that male students perceive the use of audio visual aids was good to be used in learning process, especially in learning vocabulary. Moreover, the result for the second question revealed that female students perceive audio visual aids have some benefits in learning process, especially in learning vocabulary. Then, the result for the third question asserted that audio visual aids help the students in improving their vocabulary mastery. It can be concluded that male-female EFL gave positive perceptions toward the use of audio visual in learning vocabulary and audio visual aids help the students to improve their vocabulary mastery. Besides, it is suggested for the English teacher, it is hoped that this study could be a new way in giving the new situation in the classroom. Moreover, it is suggested for the students because the most students feel helped in learning process, especially in learning vocabulary by using audio visual aids. For further researchers, the result of this study can be used as reference in the same field with the different interest.Keywords: perception, gender, audio visual aids, vocabulary, vocabulary mastery